Flower Power: An Overview on Chemistry and Biological Impact of Selected Essential Oils from Blossoms - Prosche, Sinah; Stappen, Iris (Planta Medica, 2024)
Natural raw materials such as essential oils have received more and more attention in recent decades, whether in the food industry, as flavorings and preservatives, or as insecticides and insect repellents. They are, furthermore, very popular as fragrances in perfumes, cosmetics, and household products. In addition, aromatherapy is widely used to complement conventional medicine. This review summarizes investigations on the chemical composition and the most important biological impacts of essential oils and volatile compounds extracted from selected aromatic blossoms, including Lavandula angustifolia, Matricaria recutita, Rosa x damascena, Jasminum grandiflorum, Citrus x aurantium, Cananga odorata, and Michelia alba. The literature was collected from PubMed, Google Scholar, and Science Direct. Blossom essential oils discussed in this work are used in a wide variety of clinical issues. The application is consistently described as safe in studies and meta-analyses, although there are notes that using essential oils can also have side effects, especially dermatologically. However, it can be considered as confirmed that essential oils have positive influences on humans and can improve quality of life in patients with psychiatric disorders, critically ill patients, and patients in other exceptional situations. Although the positive effect of essential oils from blossoms has repeatedly been reported, evidence-based clinical investigations are still underrepresented, and the need for research is demanded.
Keywords: Aromatherapy; odor; volatiles; health care